Exposure to phthalates: Reproductive outcome and children health. A review of epidemiological studies - Jurewicz, Joanna; Hanke, Wojciech (International journal of occupational medicine and environmental health, 2011)
Phthalates are a family of industrial chemicals that have been used for a variety of purposes. As the potential consequences of human exposure to phthalates have raised concerns in the general population, they have been studied in susceptible subjects such as pregnant women, infants and children. This article aims at evaluating the impact of exposure to phthalates on reproductive outcomes and children health by reviewing most recent published literature. Epidemiological studies focusing on exposure to phthalates and pregnancy outcome, genital development, semen quality, precocious puberty, thyroid function, respiratory symptoms and neurodevelopment in children for the last ten years were identified by a search of the PubMed, Medline, Ebsco, Agricola and Toxnet literature bases. The results from the presented studies suggest that there are strong and rather consistent indications that phthalates increase the risk of allergy and asthma and have an adverse impact on children’s neurodevelopment reflected by quality of alertness among girls, decreased (less masculine) composite score in boys and attention deficit hyperactivity disorder. Results of few studies demonstrate negative associations between phthalate levels commonly experienced by the public and impaired sperm quality (concentration, morphology, motility). Phthalates negatively impact also on gestational age and head circumference; however, the results of the studies were not consistent. In all the reviewed studies, exposure to phthalates adversely affected the level of reproductive hormones (luteinizing hormone, free testosterone, sex hormone-binding globulin), anogenital distance and thyroid function. The urinary le vels of phthalates were significantly higher in the pubertal gynecomastia group, in serum in girls with premature thelarche and in girls with precocious puberty. Epidemiological studies, in spite of their limitations, suggest that phthalates may affect reproductive outcome and children health. Considering the suggested health effects, more epidemiologic data is urgently needed and, in the meantime, precautionary policies must be implemented.